STRATEGI PENGGUNAAN MEDIA KOMIK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA BAHASA ARAB SISWA MTsN SABILURROSYAD - Rahmatunnur, Sari; Loka, Fitrah; Machmudah, Umi (Shaut al Arabiyyah, 2025)
This study to determine the strategy of using comic media in learning maharah Qiroahpada for students of class VIII MTs Sabilurrosyad Malang. Comic media is a means to convey a message through a series of images accompanied by balloons. Images in comics depict a cartoon character, for example in the form of a person, animal, plant or inanimate object. These comics are usually printed on newspapers or equipped with text. Comics began to be used to become one of the learning media to make it easier for students to understand learning. The purpose of this article is to analyze the use of comic media in learning maharah qiraah (reading skills). The method used in the research of this article is the method of data collection in qualitative research with interviews and observations. Researchers collect data by means of question and answer to the class teacher. As for the results of the interview, the teacher explained that this strategy with the use of comic media attracts students to be more enthusiastic in the teaching and learning process. Even students are more enthusiastic about learning Arabic.